Longitudinal Changes in Corneal Thickness over 8 Years: Findings from the National Institute for Longevity Sciences–Longitudinal Study of Aging Population-Based Cohort Study in Japan - Hideki Fukuoka, MD, PhD; Chikako Tange, PhD; Fujiko Ando, MD, PhD; Hiroshi Shimokata, MD, PhD; Yukiko Nishita, PhD; Rei Otsuka, PhD (Ophthalmology Science)
Purpose: To evaluate age-related changes in central corneal thickness (CCT) and investigate its relationship with other ocular parameters in community-dwelling Japanese adults through an 8-year longitudinal analysis. Design: A population-based, prospective longitudinal cohort study with baseline measurements from 1997 to 2000 and follow-up from 2006 to 2008. Subjects: A total of 631 community-dwelling Japanese adults aged 40 to 79 years (mean age: 55.7 ± 9.7 years) were enrolled from the National Institute for Longevity Sciences–Longitudinal Study of Aging. We excluded participants with corneal pathologies, contact lens use, glaucoma medication, or missing endothelial cell density measurements. Methods: Central corneal thickness was measured using calibrated specular microscopy (SP-2000; Topcon Corporation) at 2 time points approximately 8 years apart. Secondary measurements included corneal endothelial cell density, coefficient of variation in cell size, and corneal curvature. Mixed-effects models analyzed CCT changes, adjusting for sex, season, corneal endothelial cell density, and systemic health factors. Main Outcome Measures: Age-related changes in CCT, annual rate of CCT change across different age decades, and correlations between CCT changes and ocular/systemic parameters. Results: At baseline, adjusted CCT measurements were 520.2 ± 2.1 (standard error [SE]) μm, 514.1 ± 2.2 μm, 518.0 ± 2.5 μm, and 514.7 ± 3.7 μm for participants in their 40s, 50s, 60s, and 70s, respectively. Longitudinal analysis revealed a significant increase in CCT over time across all age groups (β = 0.7; SE = 0.1; P < 0.001). The annual CCT increase showed age-dependent slowing: 0.68 ± 0.08 μm for 40s, 0.62 ± 0.08 μm for 50s, 0.46 ± 0.09 μm for 60s, and 0.20 ± 0.14 μm for 70s with a statistically significant difference between 40s and 70s groups (β = −0.5; SE = 0.2' P = 0.003). Conclusions: This longitudinal analysis demonstrates that CCT increases over time in all age groups, with the rate of increase significantly slowing in older age groups. These findings contrast with previous cross-sectional studies suggesting CCT decreases with age, emphasizing the importance of longitudinal observations. These results have important implications for glaucoma diagnosis and refractive surgery safety evaluations in aging populations. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article.